Transcriptome in Combination Proteome Unveils the Phenylpropane Pathway Involved in Garlic (Allium sativum) Greening - Wu, Jinxiang; Niu, Zhonglu; Lu, Xiaoming; Tang, Xiaozhen; Qiao, Xuguang; Ma, Longchuan; Liu, Chao; Li, Ningyang (Frontiers in Nutrition, 2021)
Garlic (Allium sativum) is an important vegetable crop, widely used in cooking and medicine. The greening phenomenon of garlic severely decreases the quality of garlic and hinders garlic processing. To study the mechanism of garlic greening, a comprehensive full-length transcript sets were constructed. We detected the difference in greening between Pizhou (PZ) garlic and Laiwu (LW) garlic stored at -2.5°C and protected from light at the same time. The results showed that 60087 unigenes were respectively annotated to the NR, KEGG, GO, Pfam, EGGNOG and Swiss Prot databases, and a total of 30082 unigenes were annotated. The analysis of differential genes and differential proteins showed that PZ garlic and LW garlic had 923 differentially expressed genes (DEGs), of which 529 genes were up-regulated and 394 genes were down-regulated. Through KEGG and GO enrichment analysis, it is found that the most significant way of enriching DEGs is the phenylpropane metabolic pathway. Proteomics analysis found that there were 188 differentially expressed proteins, 162 up-regulated proteins, and 26 down-regulated proteins between PZ garlic and LW garlic. The content of 10 proteins related to phenylpropanoid biosynthesis in PZ garlic was significantly higher than that of LW garlic. This study explored the mechanism of changes at the molecular level of garlic greening and found that the phenylpropanoid metabolic pathway has an important influence on the formation of garlic green pigment. This work provides a theoretical basis for the maintenance of garlic quality during garlic processing and the future development of the garlic processing industry.